Frugivore distributions are associated with plant dispersal syndrome diversity in the Caribbean archipelagos. (8th March 2022) - Kim, Seokmin; Sales, Lilian; Carreira, Daiane; Galetti, Mauro
Abstract: Aim: Many plants rely on interactions with frugivores for dispersal, suggesting that animal communities may affect plant occupancy and diversity. However, the contribution of these interaction‐led biotic variables on plant diversity is poorly understood, especially in archipelagic hotspots such as the Caribbean. In island ecosystems, biogeographic theories suggest that island configurations drive colonization‐extinction dynamics, while macroecology argues for the importance of climatic drivers of biodiversity. Within this context, we examine how frugivore‐driven biotic factors are associated with fruiting plant species richness in relation to abiotic (climatic and geologic) and island configuration characteristics. Location: Caribbean archipelagos. Methods: We compiled a review of the diversity and distributions of 6039 plants and 326 vertebrate frugivores across 105 islands within the Caribbean. We then identified characteristics related to plant‐frugivore interactions and assigned each species as having either abiotic (wind, water, etc.) or zoochoric (frugivory‐dependent) dispersal syndromes. We related plant richness and dispersal syndromes to the regional diversity and characteristics of frugivorous animals, abiotic environments and island configuration characteristics through stepwise multivariate regression with generalized linear models and model selection. Results: We found that 44.6% of Caribbean plants are dispersed through frugivory (endozoochory). Frugivore‐related characteristics, namely accumulated body mass of island bird assemblages, were the best predictors of the diversity of seed dispersal syndromes. To a lesser degree, reptile richness and soil variety were also considered important predictors for zoochoric plant distribution, while island areas affected abiotically‐dispersed plants. Main conclusion: We found that biotic characteristics of frugivore communities are important predictors of plant diversity in the Caribbean archipelagos. However, this may also be influenced by climate and colonization history. Given the importance of biotic metrics in explaining plant diversity, we suggest that fruit‐frugivore interactions are important components of island biogeography and that frugivorous communities should be accounted for plant biodiversity predictions and forecast models.